2015
DOI: 10.1053/j.gastro.2015.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adipose Tissue Inflammation With Histologic Severity of Nonalcoholic Fatty Liver Disease

Abstract: BACKGROUND & AIMS:The prevalence of nonalcoholic fatty liver disease (NAFLD) has increased with the obesity pandemic. We analyzed the transcriptional profiles of subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT), and phenotypes and functional characteristics of adipocyte tissue macrophages (ATMs), in obese patients undergoing bariatric surgery. METHODS: We collected anthropometric data; plasma samples; and SAT, VAT, and liver tissues from 113 obese patients undergoing bariatric surgery at aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
235
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(257 citation statements)
references
References 39 publications
(17 reference statements)
14
235
1
1
Order By: Relevance
“…These data indicate that CD11c + (M1) and not CD11c − (M2) ATMs are associated with liver pathology in humans. This notion is in agreement with findings of du Plessis et al showing that CD11c + cells are more frequent in AT from patients with NASH compared with non-NASH patients and are of vital importance in NAFLD to NASH progression 11. Our human data also confirmed the data of sorted cell murine ATMs showing higher expression of neutrophil chemotaxis genes in CD11c + macrophages after HFD feeding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data indicate that CD11c + (M1) and not CD11c − (M2) ATMs are associated with liver pathology in humans. This notion is in agreement with findings of du Plessis et al showing that CD11c + cells are more frequent in AT from patients with NASH compared with non-NASH patients and are of vital importance in NAFLD to NASH progression 11. Our human data also confirmed the data of sorted cell murine ATMs showing higher expression of neutrophil chemotaxis genes in CD11c + macrophages after HFD feeding.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, CXCL1/CXCL8 and CXCL16 have been well described to recruit neutrophils in vivo, while CXCL14 is considered a strong chemoattractant of neutrophils based on in vitro assays 25 27–30. Interestingly, du Plessis et al previously described a correlation between CXCL8 and liver inflammation or NAS, further strengthening the importance of this inflammatory protein in liver pathology 11. Furthermore, inhibition of CXCL14 was shown to reduce hepatic damage and mortality in a murine hepatotoxicity model.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, metabolic and immunological processes often undergo parallel changes in normal physiology, during aging, and in various diseases. Some examples are: pregnancy-associated changes in metabolic and immune functions [46], caloric restriction-induced longevity [47], and obesity-linked metabolic impairment [48]. However, various factors that integrate adipose and immune functions in physiological and pathophysiological states are poorly understood (Box 1).…”
Section: Phb In Adipose-immune Crosstalkmentioning
confidence: 99%
“…PTX-2 is synthesised in the liver mostly upon IL-6 adipokine stimulation, and it could be hypothesised that the presence of obesity influences production of this protein. du Plessis et al 7 recently reported that in patients undergoing bariatric surgery, adipose tissue demonstrates increased expression of genes that regulate inflammation, and adipocyte tissue macrophages produce increased levels of inflammatory cytokines compared with adipose tissue from controls. Interestingly, Verna et al did not elicit a significant association between BMI and PTX-2 levels, but acknowledge that their numbers may have been too small to demonstrate a correlation.…”
mentioning
confidence: 99%